Variation of existence and location of aquaporin 3 in relation to cryoresistance of ram spermatozoa - Pequeño, Belén; Castaño, Cristina; Alvarez-Rodriguez, Manuel; Bóveda, Paula; Millán de la Blanca, María Gemma; Toledano-Díaz, Adolfo; Galarza, Diego Andres; Rodriguez-Martinez, Heriberto; Martínez-Madrid, Belén; Santiago-Moreno, Julián (Frontiers in Veterinary Science, 2023)
Introduction and objective: Osmotic changes during the process of freeze-thawing involve changes in the location of aquaporins (AQPs) in membrane domains of spermatozoa. Some AQPs, like aquaporin 3 (AQP3), are linked to sperm cryotolerance in the porcine species. Conspicuous individual variability exists between rams and their ejaculates, which may be classified as displaying good freezability (GFE) or poor freezability (PFE), depending on several endogenous and environmental factors. The present work aimed to examine whether differences in freezability could even involve changes in location and expression of AQP3 in ram spermatozoa. Methods: Thirty ejaculates from 10 rams (3 of each) were evaluated and subsequently classified as GFE (n=13) or PFE (n=17) through a principal component analysis (PCA) and k-means cluster analysis. Spermatozoa were examined for the presence, abundance and distribution of AQP3 by western blot and immunocytochemistry, employing a commercial rabbit polyclonal antibody (AQP3 - ab125219). Results and discussion: Although AQP3 was found in the sperm acrosome, midpiece, principal and end piece of the tail in both fresh and after frozen-thawed samples, its highest immunolabeling was found in the mid- and principal piece. In the GFE group, the expression of AQP3 in the mid- and principal piece was greater (P < 0.05) in frozen-thawed samples than in fresh specimens while such differences were not detected in the PFE group. Sperm cryotolerance relates to changes in AQP3 expression and thus AQP3 could be used as a biomarker for cryotolerance. Conclusion: A greater capacity of AQP3 localisation in mid- and principal piece of the spermatozoa could be linked to an increase the osmo-adaptative capacity of ejaculates with better capacity to withstand freeze-thawing processes.